Medial prefrontal cortical thinning mediates shifts in other-regarding preferences during adolescence - Sunhae Sul (Nature Portfolio, 2017)
Abstract Adolescence is a time of significant cortical changes in the ‘social brain’, a set of brain regions involved in sophisticated social inference. However, there is limited evidence linking the structural changes in social brain to development of social behavior. The present study investigated how cortical development of the social brain relates to other-regarding behavior, in the context of fairness concerns. Participants aged between 9 to 23 years old responded to multiple rounds of ultimatum game proposals. The degree to which each participant considers fairness of intention (i.e., intention-based reciprocity) vs. outcome (i.e., egalitarianism) was quantified using economic utility models. We observed a gradual shift in other-regarding preferences from simple rule-based egalitarianism to complex intention-based reciprocity from early childhood to young adulthood. The preference shift was associated with cortical thinning of the dorsomedial prefrontal cortex and posterior temporal cortex. Meta-analytic reverse-inference analysis showed that these regions were involved in social inference. Importantly, the other-regarding preference shift was statistically mediated by cortical thinning in the dorsomedial prefrontal cortex. Together these findings suggest that development of the ability to perform sophisticated other-regarding social inference is associated with the structural changes of specific social brain regions in late adolescence.